Some Factors Affecting Maze Behaviour of Drosophila melanogaster - Pluthero, Gordon Frederick (My University, 1977)
Previous experiments done by other workers indicated that associative learning in a complex maze could be demonstrated to exist for flies of some strains of Drosophila melanogaster. The experiments of this study gave similar results for the Canton S strain, however results indicative of learning, whether they are actually due to discrimination learning or pseudolearning, are only obtained for flies run through a maze with olfactory cues present in the past. The behaviour observed is shown to vary between the strains (Canton S and black) used.
Keywords: Biology; Biology